Aldehydes in relation to air pollution sources: A case study around the Beijing Olympics. (May 2015) - Altemose, Brent; Gong, Jicheng; Zhu, Tong; Hu, Min; Zhang, Liwen; Cheng, Hong; Zhang, Lin; Tong, Jian; Kipen, Howard M.; Ohman-Strickland, Pamela; Meng, Qingyu; Robson, Mark G.; et al.
Abstract: This study was carried out to characterize three aldehydes of health concern (formaldehyde, acetaldehyde, and acrolein) at a central Beijing site in the summer and early fall of 2008 (from June to October). Aldehydes in polluted atmospheres come from both primary and secondary sources, which limits the control strategies for these reactive compounds. Measurements were made before, during, and after the Beijing Olympics to examine whether the dramatic air pollution control measures implemented during the Olympics had an impact on concentrations of the three aldehydes and their underlying primary and secondary sources. Average concentrations of formaldehyde, acetaldehyde and acrolein were 29.3 ± 15.1 μg/m 3, 27.1 ± 15.7 μg/m 3 and 2.3 ± 1.0 μg/m 3, respectively, for the entire period of measurements, all being at the high end of concentration ranges measured in cities around the world in photochemical smog seasons. Formaldehyde and acrolein increased during the pollution control period compared to the pre-Olympic Games, followed the changing pattern of temperature, and were significantly correlated with ozone and with a secondary formation factor identified by principal component analysis (PCA). In contrast, acetaldehyde had a reduction in mean concentration during the Olympic air pollution control period compared to the pre-Olympic period and was significantly correlated with several pollutants emitted from local emission sources (e.g., NO2, CO, and PM2.5 ). Acetaldehyde was also more strongly associated with primary emission sources including vegetative burning and oil combustion factors identified through the PCA. All three aldehydes were lower during the post-Olympic sampling period compared to the before and during Olympic periods, likely due to seasonal and regional effects. Our findings point to the complexity of source control strategies for secondary pollutants. Highlights: The Beijing Olympic period was unique to study sources of ambient aldehyde. Three aldehydes were measured before, during, and after the Olympic period. Associations of the aldehydes with other pollutants were examined. Sources of the aldehydes were identified through principal component analysis. The source control for aldehydes require complex strategies.